Rapid and non-radioactive detection method of microsatellites in Mystus nemurus: a refined technique - Chan, Soon Choy; Siraj, Siti Shapor; Tan, Soon Guan; Mohd Yusoff, Khatijah (Universiti Putra Malaysia Press, 2005)
A simple and rapid method of DNA microsatellite isolation based on the Random Amplified Microsatellites (RAMs) PCR technique was used in this study. The work presented here is part of a continuous effort in refining and perfecting the technique for more rapid, effective and optimum productivity in single locus microsatellite marker development for the River catfish, Mystus nemurus. The current refined protocol for microsatellite isolation was able to detect a total of 135 microsatellite regions resulting in 42 unique genomic sequences being submitted to GenBank. This refined technique is able to reduce the total time required from peR cloning till sequencing specific microsatellite regions to less than three and a half months.